晚清民初文学语境下的“法国大革命”观念译介 ：以王韬、梁启超、曾朴为考察中心 (1890-1912) = Translating the concept of “French Revolution” in the literary context from the late Qing to early republican China : based on the works by Wang Tao, Liang Qichao and Zeng Pu (1890-1912) - 蒲春 Pu, Chun (2018)
法国大革命是世界史上最重要的历史事件之一，也是欧洲十九世纪最有影响力的事件之一。历史意义在于它推翻了社会等级制度中的特权及贵族阶层、颠覆了旧的社会基础、摧毁了不公平的政治结构、“废除了西方世界的封建统治格局”1、把人从不公平的社会制度中释放出来。在法国大革命后，西方社会渐渐“在自由、平等、博爱的基础之上建立了新的社会系统”2；这影响在政治体制之内，更发生在思想、政治、哲学、文学、艺术等多个方面。革命的“自由、平等、博爱”观念逐渐深入人心，“从人们的头脑中荡涤所有一贯培育尊敬服从的思想”3，更新着社会的传统和风俗。在文学领域，法国大革命所倡导的“自由、平等、博爱”成为早期浪漫主义文艺思潮的核心观念4，将西方文学推向了浪漫主义的巅峰，成为西方近 代文学最重要的思潮之一。 This thesis studies the history of how the concept of “French Revolution” was translated into China in the late nineteenth century and the beginning of the twentieth century based on the case study of the works of three translators: Wang Tao (1828-1897), Liang Qichao (1873-1929) and Zeng Pu (1872-1935). The works of the three translators present different perspectives of “French Revolution” in the literary context from 1890 to 1912. This study tracks how the concept of “French Revolution” and its principle “liberty, equality, fraternity” was deviated, distorted and restored to its original meaning in the translation from the West to the East, and further explores the causes of these changes. The national crisis in the late Qing stimulated Chinese intellectuals’ national sentiments. Learning from Western in literature constitutes an important channel for rebuilding their national power and prestige. The presentation of “French Revolution” in their works extends their personal understanding and interpretation of the concept, but also reflects the development and shaping of translated ideas in the target language in terms of ideology and values. This study aims to explore the translation phenomenon from broader perspectives — the history of literature, the history of concepts, the history of translation and the history of thoughts, and further to examine the evolution of the concept “French Revolution” in the Late Qing and Early Republic China. It also helps to reveal an important role that the translated concept plays in the social and literary progress and the interaction among them.